Amyotrophic Lateral Sclerosis – A Comprehensive Review - K, Jayavasavi.; Sukumaran, Sathesh Kumar (International Journal of Membrane Science and Technology, 2023)
Amyotrophic Lateral Sclerosis (ALS), also known as Lou Gehrig’s disease, generally said to affect people with an age between 50 years and 70 years. Signs of upper motor neuron and lower motor neuron damage, which are not explained by any other disease process, and are the reasons behind ALS. It attacks the neurons in the brain and spinal cord. These neurons transmit messages from brain and spinal cord to the voluntary muscles. At first, it causes mild muscle problems. Some people show symptoms like difficulty in walking, running, writing and speech. Eventually, the patient may lose the strength and cannot move. Due to the depletion of neuronal transmission to muscles in the chest, the patient may report difficulty to breath. The loss of lower motor neurons leads to flaccid paralysis, decreased muscle tone, decreased reflexes, muscle weakness, muscle atrophy. The defining feature of ALS is the death of both upper and lower motor neurons in the motor cortex of the brain, the brain stem, and the spinal cord. There are small eosinophilic, hyaline intra-cytoplasmic inclusions that stain positive for cystatin and transferring and are present in 70–100% of cases. Environmental and lifestyle factors play a major role in the development of ALS, but no conclusive evidence is available to support making specific changes to decrease the risk of the disease, Genetic mutations can lead to inherited ALS, which appears nearly identical to the non-inherited form. Patients with ALS generally have higher levels of glutamate in the brain, around the nerve cells in their spinal fluid. ALS patients may experience pain involving more than one type, no rigid treatment program that involves the sole use of a single agent should be employed to treat ALS-associated pain conditions. Opioids have proven to be effective in providing pain relief in advanced disease. Nevertheless, these therapies lack the ability to induce long-term lasting effects without constant administration. Over the last decade awareness of ALS has significantly increased, diagnosis is being achieved in a more timely fashion, and overall care is better. This review gives a comprehensive information about the symptoms, pathophysiology common causes, drugs currently used in the treatment.